Productive behavior of the coffee (Coffea arabica var caturra), the poro (Erythrina poeppigiana), the amarillon (Terminalia amazonia), the casha (Chloroleucon eurycyclum) in agroforestry systeMON under managements conventionals and organics in Turrialba, Costa Rica - Merlo Caballero, Marvin E. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba 8Costa Rica), 2007